Preparation of the Gubung Serut Area to be an Educational Nature Tourism Destination - Parmin; Widiatningrum, Talitha; Mursiti, Sri; Adhi, Aryono (International Journal of Community Service Learning, 2022)
This service aims to provide assistance to the community in the Gubung Serut area to prepare educational natural tourist destinations. Mentoring involves partners from PT. Astra International Tbk., Honda Central Java region. Community empowerment applies a participatory method through the stages of community empowerment through the stages of preparation, implementation, and evaluation. Preparation is carried out through the stages of establishing partnerships to build a shared commitment to developing empowerment programs in target locations. The empowerment program is prepared jointly between the service team, village officials, and target community leaders. Data during the empowerment process and activity achievements were collected through interviews and observations. Interviews reveal the opinion of tourism managers about knowledge gained during empowerment activities and benefits obtained in setting up educational tourism areas. The number of visitors to the tourist area every week has reached more than 100 people. The most attractive tourist destinations for visitors are natural panoramas and educational attractions. Preparing the Gubung Serut tourist area to become an educative natural tourism destination has been carried out through preparing management resources, building destinations, and preparing educational tourist attractions. The development of the Gubung Serut tourist area needs to be done with a broader partnership. The culinary and artistic potential still needs to involve partners more broadly to increase the diversity of tourist attractions that attract visitors.